Cultural War – Concept, Myth and Reality: A Clash of Ideas in “Post-Secular” American Society at the Turn of the Millennium (American & British Studies Annual, 2014)
The idea of culture war has been used in various analyses focused on the transformation of modern society in general and especially regarding America since the 1980’s. This concept underlies the “ideological schism” demonstrated by the polarizing debates in the American public sphere. These disputes have involved a wide spectrum of disagreements about for example the relationship between church and state, multiculturalism, abortion and gay marriage. This paper will analyze the concept of cultural war and the usage of the term in the ideological struggle between liberal and conservative streams in contemporary American politics. It will also consider the sustainability of this concept for scientific reflection, especially with regards to the description and interpretation of the religious situation in American society.
Keywords: cultural war; ideology; fundamentalism; liberalism; religion; politics; American society